Археологічне та археомагнітне датування волинцевських комплексів Ходосівського поселення - Комар, О.В. (Археологія і давня історія України, 2018)
У статті здійснено верифікацію результатів археомагнітного датування двох жител волинцевської культури з поселення Ходосівка-Козаків яр за допомогою сучасних археологічних даних та програмного додатку Matlab tool for archaeomagnetic dating. In 1972, two ovens from dwellings of the Volyntseve culture were studied with archaeomagnetic method by G. F. Zagnii. Proposed archaeomagnetic dating for the oven from Khodosivka dwelling 2 («6th century AD») was different from the archaeological date for two centuries, thence both archaeomagnetic dates seemed unreliable and they were never used in archaeological research as a chronological marker for the Volyntseve culture. The task of this study was to determine whether it is possible to verify old archaeomagnetic data with the help of modern analysis tools and to compare it with recent archaeological datings of the same complexes. Finds from Hodosivka dwellings 1 and 2 include iron buckle, belt ornament, earring, glass beads of the Saltiv cultural circle and wheel-made pottery of the Saltiv technology, that allows using detailed chronological scale of the Saltiv culture and limiting the chronological framework for dwellings 1 to 790—835 AD and for the stratigraphically earlier dwellings 2 to 740—790 AD. Analysis of archaeomagnetic data was made with Matlab tool for archaeomagnetic dating software and three global models: ARCH3K.1, SHA.DIF.14K and CALS3K.3. Two versions of the archaeomagnetic data were examined. First version of data (1977) presented only declination and inclination values, calculated with larger number of measured samples accepted; later version (1986) reflects data with fewer samples accepted after the procedure for excluding extreme values and also field intensity values. Comparison showed that the later version of the data is much better consistent with archaeological dates and must be used as basic. The results of 95 % probability archaeomagnetic dating of the dwelling № 1 in all three used models ARCH3K.1, SHA.DIF.14K and CALS3K.3 are in good agreement with archaeological date: respectively 752—845; 758—855; 678—858 AD. Agreement is less precise in archaeomagnetic dating of the dwelling № 2: respectively 677—784; 702—802; 622—745, 770—814 AD, where only the second part of the time range corresponds to the archaeological dating. However, both new results are acceptable, which means the presence of a chronological error in the local archaeomagnetic curve of G. F. Zagnii and O. M. Rusakov, created for the territory of Ukraine and Moldova. This conclusion means that all Early Mediaeval chronological schemes in archaeology based on this archaeomagnetic curve needs verification of archaeomagnetic data using modern databases and global models.